Mobile Apps Engineering : Design, Development, Security, and Testing - Mostefaoui, Ghita K., editor; Tariq, Faisal, editor (Boca Raton, FL : CRC Press, 2019)
"The objective of this book is to gather best practices in the development and management of mobile apps projects. It will provide the concepts, architectures, models, and key technologies, which are required to achieve successful mobile apps projects. It will emphasize essential concepts and their application to real life problems. The book will cover requirements gathering and analysis, mobile device operating systems, design patterns, development tools, languages, and technologies, as well as other fundamental concepts. It will also examine quality and testing procedures for mobile apps, along with providing software engineering case studies"